Are Nutrition-Related Knowledge and Attitudes Reflected in Lifestyle and Health Among Elderly People? A Study Across Five European Countries - Jeruszka-Bielak, Marta; Kollajtis-Dolowy, Anna; Santoro, Aurelia; Ostan, Rita; Berendsen, Agnes A. M.; Jennings, Amy; Meunier, Nathalie; Marseglia, Anna; Caumon, Elodie; Gillings, Rachel; de Groot, Lisette C. P. G. M.; Franceschi, Claudio; et al. (Frontiers in Physiology, 2018)
Background: Nutrition-related knowledge (NRK) and nutrition-related attitudes (NRAs) are necessary for dietary changes towards healthier dietary patterns. In turn, healthier dietary patterns can be beneficial in maintaining health of older adults. Therefore, the aim of this cross-sectional study was to investigate whether NRK and NRAs were associated with lifestyle and health features among older adults (65+ years) from five European countries (France, Italy, Poland, the Netherlands and United Kingdom). Methods: Within the European project NU-AGE, 1,144 healthy elderly volunteers (65-79 years) were randomly assigned to two groups: intervention (NU-AGE diet) or control. After one-year of follow-up, both NRK and NRAs were assessed during exit interviews, in combination with a number of lifestyle and health variables (e.g., physical activity, smoking, alcohol use, BMI, self-assessed health status). Multivariable linear regression models were used in data analysis. Results: In the NU-AGE study sample, good NRK was associated with lower BMI and higher physical activity. More positive NRAs were related to lower BMI and self-reported very good or good appetite. Moreover, both NRK and NRAs were associated with some socio-economic determinants, like financial situation, age, education, living area (for NRK), and country (for NRAs). Participants in the intervention group showed a better NRK (β=0.367 [95% CI: 0.117; 0.617], p=0.004) and more positive NRAs (β=0.838 [95% CI: 0.318; 1.358], p=0.002) than those in the control group. Higher self-evaluated knowledge was also significantly related to more positive NRAs (p<0.001). The most popular sources of nutrition information were food labels, books and magazines on health, the dietitian and the doctor’s office, although their importance varied significantly among countries, and, to a lesser extent, between women and men and between intervention and control group. Conclusion: Higher NRK and NRA scores were associated with lower BMI and higher physical activity level. Therefore, a good nutrition-related knowledge and positive nutrition-related attitudes can strongly and positively influence the health status and quality of life among the older population. These results offer a great opportunity for policy makers to implement educational programs in order to counteract the epidemic of obesity and to improve the health span of European population.